Income generating workshop - series 1,2 and 3 - Hazlina, Faizal (Penerbit UMP, 2014)

(untitled)
KRA 2: Financial sustainability is defined as 'The ability of an organisation to manage development activities and unexpected financial problems without drastic modifications in managing the expenses and generating income'. It is led by a Champion and assisted by a Facilitator and a Secretariat.